MiR‐425‐5p is negatively associated with atrial fibrosis and promotes atrial remodeling by targeting CREB1 in atrial fibrillation. Issue 2 (February 2022) - Wei, Feiyu; Ren, Wenjun; Zhang, Xi; Wu, Peng; Fan, Jie
Highlights: The miR-425-5p was downregulated in the plasma and atrial tissue in atrial fibrillation (AF) patients. Downregulation of miR-425-5p was associated with left fibrosis in persistent AF. Catheter ablation could restore decreased plasma miR-425-5p. Downregulation of miR-425-5p could promote atrial remodeling by targeting CREB1. Abstract: Background: Progression of atrial fibrosis is vital for atrial remodeling in atrial fibrillation (AF). The main objective of the present study was to explore the association between miR-425-5p and atrial fibrosis as well as the resultant impact on atrial remodeling in AF. Methods: Firstly, miRNAs sequencing and quantitative real-time polymerase chain reaction was used to screen and verify the miRNAs expression level in plasma and atrial tissue in AF patients. The left atrial fibrosis was evaluated with the left atrial low voltage area by using left atrial voltage matrix mapping. Cell counting kit-8 was used to detect fibroblasts proliferation. The AF mouse model was established using acetylcholine-CaCl2 injection for 7 days. Target gene prediction software, luciferase assay, and western blotting were employed to confirm the direct targets of miR-425-5p. Results: Firstly, we demonstrated that miR-425-5p was downregulated in plasma and atrial tissue among the patients who suffered from AF. We then confirmed that the plasma's miR-425-5p level was negatively correlated with left atrial fibrosis in persistent AF, and catheter ablation could restore the decreased plasma miR-425-5p. Besides, receiver operating characteristic curve analysis revealed the miR-425-5p not only could differentiate AF from healthy control wit area under the curve (AUC) 0.921, but also discriminated persistent AF from paroxysmal AF with AUC 0.888. Furthermore, downregulation of miR-425-5p could promote atrial remodeling, and overexpression of miR-425-p could improve atrial remodeling and decrease susceptibility to atrial fibrillation. Finally, CREB1 was verified to be a direct target for miR-425-5p. Conclusions: Our findings suggested that miR-425-5p could serve as novel atrial fibrosis biomarker and contributed to atrial remodeling in AF. Graphical abstract: Graphical abstract Image, graphical abstract